Social Media for English Teaching and Learning: A Bibliometric Analysis of Research Publications (2012–2023) - Urai Salam; Erica Ikramunnisa; Yanti Sri Rezeki; Carla Queiroz (International Journal of Pedagogy and Teacher Education, 2025)
This study presents the first comprehensive bibliometric analysis exploring the role of social media in English Language Teaching (SM-ELT) in Indonesia between 2012 and 2023. A total of 2,652 articles were initially retrieved from the Garuda database. After applying rigorous inclusion criteria—focusing on the Indonesian context, journal publications, and English-language articles—687 publications were analyzed. The findings reveal a steady increase in publication volume, with 79.5% of the studies published during the COVID-19 pandemic, primarily investigating students’ perceptions of social media in online learning. YouTube was identified as the most frequently studied platform (124 occurrences), followed by TikTok (78), with a noticeable decline in Facebook usage. The analysis also highlights the most cited journals (e.g., SELTICS with 282 citations) and prolific authors (e.g., Wahyudin with 300 citations), reflecting strong research networks within Indonesian institutions. Using VOSviewer, co-word and temporal analyses identified key research clusters, including writing skills, vocabulary acquisition, students’ perceptions, and pedagogical innovations such as blended and project-based learning. The study suggests that TikTok will continue to grow in relevance due to its engaging, short-form content and appeal to younger learners. However, it also cautions that the rise of Artificial Intelligence (AI) tools may shift the focus away from social media platforms, offering potentially more effective and scalable solutions for language education. Therefore, future research should explore the intersections between AI and social media in ELT. This bibliometric study provides a foundation for scholars and educators to navigate evolving digital landscapes in English language education.